Art Music by Caribbean Composers: St. Vincent and the Grenadines - Gangelhoff, Christine; LeGrand, Cathleen (International Journal of Bahamian Studies, 2013)
Traditional music includes string band, quadrille and bélé (Embassy, 2013). String bands and fife-and-drum bands are common on St. Vincent; quadrille and other ballroom music are often performed by such ensembles (Bilby & Neely, 2009). Quadrille is particularly popular in north-eastern parts of St. Vincent, where a large number of the residents are descended from the original Carib inhabitants of the island.